(3GdGJUGd GdJQHhj (B/s - (3GejQI, Ydj eMeOs ([(3Ohf ecGf(B] :s (3GdOGQ GdYGdejI ddfTQ h GdJhRjY ,s, 2006)
(3GdGJUGd ef hXGFa GdEOGQj GdJj jJe YHQgG GdbjGe HXGFa GdEOGQI GdCSGSjI h dPdc aGdGJUGd GSGSj dhLhO CjI LeGYI HGYJHGQg hSjdI GaQGOgG dJHGOd GdeYGfj h GdCacGQ YdeG HGf GdGJUGd dGjbhe abW Ydi fbd GdeYGfj h dcf GjVG Ydi agegG h gh GjVG eXgQ gGe aj MjGI GdGfSGfs
(3HHdjhZQGajG (B: (3U(B.176-180s
Keywords: (3GdGJUGds; (3GdGJUGd GdJQHhj s